A escola pilchada: o uso da educação e das políticas públicas pelo MTG - Conceição, Ricardo da (2019)
This work is dedicated to the analysis of the use of public policies by the Gaucho Traditionalist Movement, in the most diverse public areas of Rio Grande do Sul, especially in the area of education. To this end, propositions and theses presented at the Traditionalist Congresses, organized by the Gaucho Traditionalist Movement, which aim at policy demands in the state of Rio Grande do Sul are analyzed. It is also analyzed how the demands of the Gaucho Traditionalist Movement are actually implemented in the State policies of Rio Grande do Sul. It also analyzes how Gauchism emerged and spread throughout history, and how it has now become one of the state's main political and economic forces. It is also analyzed how the purposive actions of the Gaucho Traditionalist Movement find in the schools ample space for its implementation, with numerous activities developed by entities and subjects linked to the Movement. The documentation analyzed is part of bibliographical publications of the Gaucho Traditionalist Movement, as well as digital publications of portals, websites and blogs linked to MTG. From the analysis of the founding documents of the Gaucho Traditionalist Movement and propositions presented in Traditionalist Congresses, it can be concluded that the Movement is understood as a public utility organ, being able to assist the State in its problems. Since MTG is sometimes understood as an integral part of the state structure, proposing actions, laws, manuals using direct actions in certain areas. Also, that the movement understands that its action is necessary for the education of children and young people with the introduction of traditionalist principles in school, relying on an imaginary resort and imposing a unique culture on all, disregarding the multiculturalism that forms the state of Rio Grande. Thus, the movement finds fertile ground in education and schools for the implementation of its demands.